Participatory qualitative research methodologies in health - Higginbottom, Gina; Liamputtong, Pranee 1955- (Sage Publications Ltd, 2015)
This guide to the essentials of doing participatory methods in a broad range of health contexts covers all of the stages of the research process, from research design to dissemination